RADIKALISME DALAM ISLAM ANTARA PALEBELAN DAN KONSTRUKSI SOSIOLOGI - STAIN Surakarta, Muh. Fajar Shodiq (GEMA, 2015)
The acts of muslim extremists in recent years, from hostage taking and kidnappings to the world trade center and pentagon attacks of 9/11, lead many to ask why islam dan muslims are violent. Islam from the quran to islamic law, does not permit and in some circumstances even requires the use of force in self-defense or the defense of islam and islamic community. however there is often a fine line between legitimate and illegitimate use of force, defensive and offensive battle dan warfare, resistanace and terrorism while relegion can be wonderful force for good historically it has also been used to legitimate violence and warfare. TheÂ  three great monotheistic traditions from biblical times to the present represent long histories of the positive and negative power of religion its ability to create and destroy.